Answer:
-11
Explanation:
Start off with the meaning of f(x) = 5x - 1
The notation is used to tell us that when a number is put in for the x on the left, it is put in every x on the right as well. The left x comes first then what to do with it on the right gives the answer. So watch it happen.
f(-2) means that wherever you see an x on the right, put in -2 for it.
f(-2) = 5*-2 - 1
f(-2) = -10 - 1
f(-2) = - 11
No matter how complicated what is on the right, the rule is the same.
f(x) = x^5 - 4x^3 - x
f(-2) = (-2)^5 - 4*(-2)^3 - 2 would be how you interpret that question.
f(-2) = -32 + 32 - 2
f(-2) = -2